Improved hydrogen production from pharmaceutical intermediate wastewater in an anaerobic maifanite-immobilized sludge reactor. Issue 53 (15th October 2021) - Liu, Ruina; Lin, Youwei; Ye, Xiaodong; Hu, Jinzhao; Xu, Gongdi; Li, Yongfeng
Abstract : An anaerobic maifanite-immobilized sludge reactor was used to investigate continuous hydrogen production for treatment of pharmaceutical intermediate wastewater at different organic loading rates according to changes in the hydraulic retention time. Abstract : A novel anaerobic maifanite-immobilized sludge reactor (AMSR) was employed to investigate the feasibility and performance of continuous hydrogen production for the treatment of pharmaceutical intermediate wastewater (PIW) at different organic loading rates (OLR) (from 12 to 96 g COD L −1 d −1 ) according to changes in the hydraulic retention time (HRT). A reactor without maifanite was also employed as a control. The results indicate that maifanite accelerates granular sludge formation and the AMSR presents more efficient and stable performance than the control in terms of the hydrogen production rate. In the AMSR, the highest hydrogen production rate of 11.2 ± 0.4 mmol L −1 h −1 was achieved at an optimum OLR of 72 g COD L −1 d −1 . The main metabolic route for hydrogen production was ethanol-type fermentation, which was reflected in the relative abundance of E. harbinense, which was dominant for all of the OLRs. The maximum energy conversion efficiency in the dual production of hydrogen and ethanol was determined to be 24.5 kJ L −1 h −1 at an OLR of 72 g COD L −1 d −1 .